Preserving Heritage: An Analysis of Marriage Literature and Adat in Bone - Feby Triadi (JURNAP: Jurnal Administrasi Publik, 2024)
This study examines traditional marriage literature in Bone, focusing on its role in preserving cultural heritage, guiding ritual practices, and maintaining social norms. Using an ethnographic approach, the research analyzed lontara manuscripts, oral narratives, and field observations to uncover the symbolic meanings, procedural guidelines, and societal functions embedded in local marriage customs. Data were collected through document analysis, semi-structured interviews with community elders, and participant observation of marriage ceremonies. Findings indicate that marriage literature in Bone functions as a codified guide for ritual conduct, social hierarchy, and intergenerational value transmission, reflecting both historical continuity and adaptive cultural practices. The study highlights the significance of traditional literature as a medium for preserving adat values and sustaining community identity.